Dampak Parkir Khusus Wisata Terhadap Simpang Bersinyal Jalan Perkotaan: Studi Kasus Persimpangan Ngabean, Yogyakarta - Noor Mahmudah; Adhytia Tubagus (Universitas Muhammadiyah Yogyakarta, 2015)
The development of Special Region of Yogyakarta has been occuring rapidly due to this region is well known as student city and the primary tourism destination in Indonesia. One of the transportation problems related to the tourism activities is traffic conflict due to parking area of tourism bus in Ngabean, Yogyakarta City. Therefore it is needed to evaluate signalized junction around the parking area in order to reach the optimal performance. The study carried out among other by conducting field survey to the existing condition (performance) of signalized junction either in the weekend (Saturday) and weekday (Monday), especially by evaluating the degree of saturation (ds). The analysis results showed that the degree of saturation in the weekend is 0,89, which is higher than the allowed one (ds=0,85). Since the degree of saturation in the weekday is 0,76 so it is relatively good. The scenarios (model) applied to improve the overall junction performance are by estricting (prohibiting) left turning on red (LTOR) and by carrying out road widening. The final result obtained from the scenario (model) is the degree of saturation (ds) becomes lower than the allowed value (0,830,85) for all approaches in the signalized junction.